Step up - Tatum, Channing; Fletcher, Anne.; Dewan, Jenna; Radcliff, Damaine; Washington, De'Shawn.; Mario, 1987-; Seresin, Michael; Zigman, Aaron; Touchstone Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) (Burbank, CA : Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
Tyler is a rebel from the wrong side of Baltimore£s tracks. The only thing that stands between him and an unfulfilled life are his dreams of one day making it out of there. Nora is a privileged ballet dancer attending an elite school of dance in Baltimore. The only thing standing in the way of her brilliant future is finding a great dance partner for her senior showcase.
English track: Dolby digital 5.1 surround.
Special features: deleted scenes and bloopers; MySpace.com dance contest videos; 'Making the moves' featurette; music videos; audio commentary.
Director of photography, Michael Seresin ; editor, Nancy Richardson ; music, Aaron Zigman ; costume designer, Alix Hester ; production designer, Shepherd Frankel.
Channing Tatum, Jenna Dewan, Damaine Radcliff, De'Shawn Washington, Mario, Drew Sidora, Rachel Griffiths, Josh Henderson, Tim Lacatena.
MPAA rating: PG-13; for thematic elements, brief violence and innuendo.
DVD.
Keywords: Dancers -- Maryland -- Baltimore -- Drama; High school students -- Conduct of life -- Drama; Community service (Punishment) -- Maryland -- Baltimore -- Drama; Films for the hearing impaired; Feature films; Musical films